Peningkatan Aktivitas Menjawab dan Kualitas Jawaban Mahasiswa dengan Pertanyaan Prompting pada Mata Kuliah Strategi Pembelajaran Kimia - Guspatni, Guspatni; Andromeda, Andromeda; Bayharti, Bayharti (JURNAL EKSAKTA PENDIDIKAN (JEP), 2018)
This classroom action research aimed to increase studentsâ answering activity and quality of the answer to questions asked in Strategi Pembelajaran Kimia course. This research was done in two cycles each consisting of planning, action, observation, and reflection phases. Instruments used in this research were observation sheet and questionnaire. Prompting questions had been designed for each meeting. Primary action given was asking prompting questions in learning. Two observers did observation and lecture was recorded with camera. Observation data from observers and camera recording were analyzed descriptively to get percentage of students who answered question before and after prompting was given as well as to get percentage of keywords in the answer given by students. The result showed that studentsâ answering activity increased after prompting was given. The quality of the answer got better with prompting questions as well. The aid of visual media given in the next cycle showed that students dared to explain concepts they had not been familiar with. Other actions that increased studentsâ answering activity were time and reward givings. Data from questionnaire distributed at the end of the course showed that students like prompting questions because they could understand the question and concept asked and then find the answer.